Eddy Kinetic Energy in the Arctic Ocean From a Global Simulation With a 1‐km Arctic. Issue 14 (17th July 2020) - Wang, Qiang; Koldunov, Nikolay V.; Danilov, Sergey; Sidorenko, Dmitry; Wekerle, Claudia; Scholz, Patrick; Bashmachnikov, Igor L.; Jung, Thomas
Abstract: Simulating Arctic Ocean mesoscale eddies in ocean circulation models presents a great challenge because of their small size. This study employs an unstructured‐mesh ocean‐sea ice model to conduct a decadal‐scale global simulation with a 1‐km Arctic. It provides a basinwide overview of Arctic eddy energetics. Increasing model resolution from 4 to 1 km increases Arctic eddy kinetic energy (EKE) and total kinetic energy (TKE) by about 40% and 15%, respectively. EKE is the highest along main currents over topography slopes, where strong conversion from available potential energy to EKE takes place. It is high in halocline with a maximum typically centered in the depth range of 70–110 m, and in the Atlantic Water layer of the Eurasian Basin as well. The seasonal variability of EKE along the continental slopes of southern Canada and eastern Eurasian basins is similar, stronger in fall and weaker in spring. Plain Language Summary: Ocean mesoscale eddies play crucial roles in the ocean, climate, and ecosystem. While this is presumably also true for Arctic eddies, their dynamics and impacts are far less understood than for lower latitudes: It is a great challenge to resolve the very small Arctic eddies in numerical simulations. Just now, owing to the development of new‐generation models, it becomes possible to resolve Arctic eddies in realistic global ocean configurations. The study presents the results from a first‐ever decadal‐scale global simulation with the Arctic Ocean at 1‐km resolution. An overview of the eddy kinetic energy and its generation is provided for the Arctic deep basin, with a focus on both spatial and seasonal variability. The current results fill some knowledge gaps in Arctic eddy energetics, and also help to identify questions that we will be able to answer with such frontier simulations in the future. Key Points: A decadal‐scale global simulation with the whole Arctic Ocean at 1‐km resolution is carried out using FESOM2 A basinwide overview of Arctic eddy energetics is provided with a focus on spatial patterns and seasonal changes of eddy kinetic energy Continental slopes in southern Canada and eastern Eurasian basins are the most energetic regions featuring similar seasonality